MODEL SISTEM PENYELENGARAAN KEOLAHRAGAAN DI KABUPATEN INDRAMAYU SEBAGAI UPAYA MENINGKATKAN PRESTASI ATLET - Kusumah, Riva Rachmi; Siregar, Syamsul Bahri (Universitas Wiralodra, 2022)
This study is to analyze and describe the duties, obligations and authorities of local governments based on the provisions of laws and regulations regarding the implementation of sports in the regions where local governments, both provincial and district/city governments, namely in carrying out sports administration can determine and implement sports policies in the regions. based on sports policies and coordinate, supervise, and evaluate the implementation of sports policies in the regions based on sports policies. Local governments implement sports policies by considering regional potential and regional conditions. In addition, in an effort to improve sports achievement in Indramayu Regency, various influential factors emerged, both supporting or hindering. Factors that are supportive are consistent coaches, quality athletes, assistance from the private sector, and the implementation of sporting events. While the inhibiting factors are limited facilities and infrastructure, stunted regeneration of athletes, and funding and these problems in some of the obstacles to athlete achievement, the local government can establish policies in the form of regional regulations.